A study to determine and compare dimorphic trait of mandibular canine between Gujarati and non-Gujarati populations - Himanshu Shrivastava; Nidhi M Shah; Rumiya Aysha; Mitul Shah; Nareen Chakravarthy; Santosh R Duliganti (Wolters Kluwer Medknow Publications, 2020)
Introduction: Among all teeth, mandibular canine shows greatest variation in dimensions between the sexes, a phenomenon known as sexual dimorphism. This can be immensely beneficial to the forensic investigator for the purposes of both investigation and identification, as it significantly narrows down the possibilities, as the probable perpetrators and/or victims are concerned. Sex identification is an absolute necessity in cases of suicide, homicide, mass, casualties (both manmade or natural), and a tooth, which shows obvious sexual dimorphism can be a useful means of personal identification, especially where there has been extensive decomposition or destruction of facial soft tissue features. Another facet of forensic investigation is identification of racial origin. So, any odontometric parameter showing significant racial divergence can be used as a means of identification. Aim and Objective: The aim of this study was to determine and compare cervico-incisal heights and mesiodistal widths of both mandibular canines of the Gujarati and non-Gujarati subjects under study. Materials and Methods: The study sample involved 100 participants, divided into four groups, each of the four groups included 25 participants, representing Gujarati males, Gujarati females, non-Gujarati males, and non-Gujarati females, respectively. Results: When we compared the mesiodistal and cervico-incisal dimensions of the mandibular canine, both right and left, Gujarati males were found to possess significantly larger sized teeth in comparison to their female counterparts, and the same results were replicated for non-Gujarati males vis-a-vis their female counterparts. Non-Gujarati males and non-Gujarati females were found to have significantly higher odontometric values in comparison with their Gujarati counterparts. Conclusion: Gujaratis have smaller sized mandibular canine in comparison with non-Gujaratis. However, studies comparing specific groups are required, as non-Gujaratis are a diverse racial group.